2004
DOI: 10.1080/10584580490895680
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Microwave Dielectric Properties of (Sr,Ba)Nb2O6 Thin Films

Abstract: 001) oriented (Sr,Ba)Nb 2 O 6 (SBN) thin films were deposited on MgO (001) single crystal substrates by the pulsed laser deposition method. Structural properties of SBN films were investigated using X-ray diffractometer. The microwave dielectric properties of SBN films were examined by calculating the scattering parameter obtained using a HP 8510C vector network analyzer with the frequency range 0.5-20 GHz at room temperature under the dc bias field of 0-80 kV/cm for interdigital capacitors (IDT) and coplanar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A value of 0.25% cm/kV at low frequency (1MHz) was recently presented as an excellent result for BST thin films (Nozaka et al, 2008). The electrical tunability of SBN thin films prepared by PLD on MgO substrates has been measured by Moon et al between 0.5 and 20 GHz and found to be 0.5% cm/kV (Moon et al, 2004). The same authors compared phase shifters based on (Ba, Sr)TiO 3 and SBN thin films between 0.5 and 20 GHz, and concluded that these two materials were competitors for microwave tunable devices (Moon et al, 2005).…”
Section: Sbn Thin Films: Dielectric Propertiesmentioning
confidence: 92%
“…A value of 0.25% cm/kV at low frequency (1MHz) was recently presented as an excellent result for BST thin films (Nozaka et al, 2008). The electrical tunability of SBN thin films prepared by PLD on MgO substrates has been measured by Moon et al between 0.5 and 20 GHz and found to be 0.5% cm/kV (Moon et al, 2004). The same authors compared phase shifters based on (Ba, Sr)TiO 3 and SBN thin films between 0.5 and 20 GHz, and concluded that these two materials were competitors for microwave tunable devices (Moon et al, 2005).…”
Section: Sbn Thin Films: Dielectric Propertiesmentioning
confidence: 92%
“…In this case, strontium barium niobate Sr x Ba 1−x N 2 O 6 (SBN) looks more attractive compared to BST in terms of the dielectric nonlinearity, since the smaller niobium ion provides a greater ionic displacement than the titanium one (R Nb = 0.69 Å < R Ti = 0.75 Å) [7,8]. In addition, strontium barium niobate in thin film form exhibits high permittivity values at 2 of 13 relatively low losses at microwaves [9], which makes it promising as a nonlinear material of tunable microwave devices.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, much fewer articles are devoted to the study of the dielectric and tunable properties of strontium barium niobate [31]. Today, studies on the dielectric properties of SBN films grown on silicon [32,33], magnesium oxide [9,34], and strontium titanate substrates [35,36] have been published. The vast majority of the mentioned publications provide data on the dielectric properties of SBN films in the frequency range of 1-100 kHz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation